THE USE OF SCREEN PRINTED ELECTRODE-BASED NANOSENSOR TO DETECT DRUGS IN BBPOM DENPASAR, BALI - Tahta Amrillah; Mirza Ardella Saputra; Prastika Krisma Jiwanti; Ilma Amalina; Raden Joko Kuncoroningrat Susilo; Suhailah Hayaza; Fadjar Mulya; Mochamad Lutfi Firmansyah; Retno Sari (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Nanotechnology sensor is one of technology that could support biomedicine developments, including in the pharmaceutical field. Highly sensitive sensor having ability to detect various pharmaceutical substances as well as components in the food have have been developed, including the so-called nanosensor based screen printed electrode, using nanomaterial boron doped diamond (BDD). This nanosensor could replace conventional sensing technology that is considered still have several drawbacks such as inefficient routes and time consuming, as well as high cost. A nanosensor-based screen printed electrode was developed and implemented for detection of pharmaceutical substances, including drugs. In this opportunity, this community service program disseminated nanosensor technology to pharmacists and food and drug assessors at BBPOM Denpasar, Bali. The program is conducted via short course and practical case on how to use the nanosensor that already developed in the laboratory. The community service program is started with pretest about sensor and nanotechnology, followed by course, practical case, and lastly, the post-test. The post-test results showed a highly positive response, with 71% of participants reporting very high interest, 66% expressing very high satisfaction, and the majority indicating that the activity was relevant, beneficial, and worth recommending. These community service activities are expected to facilitate the broader implementation of nanosensor technology in drug and food assessments. Hopefully, this technology could be spreadly used by the the pharmacies and stake holders who have the right for doing drug and food assessements, not only in Denpasar but also in other cities in Indonesia.